HUBUNGAN ANTARA KONSUMSI ENERGI DAN PROTEIN DENGAN STATUS GIZI PADA IBU HAMIL DI WILAYAH KERJA PUSKESMAS I SUKOHARJO - Hasri . Yuliantini; Mifbakhuddin . . (Jurnal Kesehatan Masyarakat Indonesia, 2004)
ABSTRACT Background: Monitoring nutrition status for pregnant women is a method to know the health condition of pregnant women. Many researchers have shown that women who suffer lack of energy or protein consumption, before or during pregnancy will affect on fetus development. Objective : to analyze the correlation between energy and protein consumption degree and nutrition status on pregnant women in Public Health Center (Puskesmas) I Sukoharjo. Method : This explanatory research is alone by using survey method and cross sectional approach. Population of this research is pregnant women in Puskesmas I Sukoharjo area which get anemia prevention project from Health Department of Sukoharjo region in 2003. There are 40 pregnant women who will be observed. All samples that are observed to measure nutrition status are by using arm circumference (L|LA) method and recall method for 3X24 hours to know energy) and protein consumption. Data is analyzed statistically by using Pearson's Product Moment test based on the significant level 5'%. Result; This research shows: the average of energy consumption is 1820,15 Kkal per day (73,24% RDA), with the highest rate is 2663,1 5 Kkal/hr ( 107,16% RDA), and the lowest rate is I I99 Kkal/hari (48,24% RDA). There is significant correlation between energy consumption with nutrition status on pregnant women (p:0,001). The average protein consumption is 48,55 gr per day ( 80,9% RDA), with the highest is 76,10 gram per day (126,83% RDA), and the lowest is 33,1 grt/hr (80,9%AKG). Protein consumption correlated significantly with nutrition status on pregnant women (p:0,032). Conclusion : The average energy and protein consumption on pregnant women is still under RD/ (Recommended Dietary Allowance). Energy and protein consumption is correlated significantly with nutrition straits. Keywords : Nutrition status, protein , energy consumption